VALUE DEVELOPMENT IN HISTORY LEARNING THROUGH PARIBASA AND BABASAN - Mulyana, Agus; Darmawan, wawan (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2013)
This research derived from an anxiety that looked history learning as a subject that was very close with intellectual competences development. In fact, history itself ilustrated value experience which could give such a kind of wisdom, and more over the history also had a big value in it. So, it was thought that there was a need to have a right strategy to understand the value of history. One kind of value that could be internalized to students in history learning was Sundane local wisdom. Sundanese culture had various inheritances, for example was like oral literature (folklore) in paribasa and babasan. The problems in this research were how to identify the values of Sundanese culture in paribasa and babasan, and how the people could use paribasa and babasan in a process of value socialization and internalization, how those values could be applied in history learning. This research used a qualitative approach. It was divided in two phases, the first one was about folklore, and the second one was about naturalistic study on history learning process in the class. The result of this research was also divided in two parts. The first part was related to social values identification that could be extracted on Cireundeu Cultural Village pass through paribasa and babasan. Based on the result of the observation and interview with the villagers, they used paribasa and babasan which generally got the same point with the others Sundanese societies, so there was no specialty in Cireundeu. The main point was they still used paribasa and babasan in their daily life, especially when they counseled their children, interacted to each other, said euphemism critic, and taught Sundanese values to the young generations. Second, this part was related to paribasa and babasan’s value implementation in history learning on SMA Pasundan 1 Bandung. There were two approaches in this implementation, value inculcation approach and value clarification approach. This kind of history learning that put paribasa and babasan as a media of value inculcation passed through appreciation, self-identification, behavior implementation, and habit forming